Benefits of ethnic games and sports for coordination skills in beginner rifle shooting sport - Vinokurova, N. A.; Vasilieva, M. I.; Pavlova, A. D. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to test and analyze benefits of a coordination skills building model for beginner shooters with elements of ethnic games and sports. Methods and structure of the study. Progress of the sample in coordination skills and physical fitness was tested in the experiment by a standard test toolkit including the 4x9m shuttle cubes-carrying sprint test, Romberg's test and Yarotsky's test. We used SKATT shooting simulator to rate individual progress by the practical rifle shooting tests. We sampled for the coordination skills building model testing experiment the 11-14 year-old beginner shooters (n=14) with 1-2-year training records and split them up into EG and RG. The EG was trained as required by the new coordination skills training model with the ethnic sports elements, whilst the RG training was standard. We selected the following ethnic sports elements for the coordination skills training in the EG: - "Lean Cow Raise" to build leg strength, coordination and balance; - "Oybontonuulaain" (Watering) to excel coordination skills, joint motility and dexterity; and - "Tutumergir" (Spinner) to train flexibility, coordination skills and grip strength; The trainings were complemented with the table folk game "Khabylyk" (Chips), one of the most ancient ones played with splinters used by every Yakut family to make fire, and known to excel eye accuracy, thinking skills and fine finger movements; and "Khaamiska" (Pebbles) game with "five pebbles" popular the world over in different versions with the only local difference that the 1x1.5cm wooden cubes are used instead of natural pebbles. Results and Conclusion. The new coordination skills building model for beginner shooters with elements of ethnic sports and games was tested beneficial for the theoretical and practical trainings. Prudently designed and managed ethnic sports elements are recommended for application in shooting sports as they help excel coordination skills, discipline, diligence, dedication, endurance and perseverance. The ethnic sports and games are highly effective for physical activation in idle times, mental health protection and improvement and healthy lifestyle cultivation purposes, with special benefits for easily trained coordination skills, provided the training systems are well designed and managed on a progress-customized basis. The pre- versus post-experimental tests in the EG and RG found the ethnic sports elements being highly beneficial for beginner rifle shooters as verified by the fast and stable progress in practical shooting tests.